THE INFLUENCE OF CARBIMAZOLE ON SERUM LEPTIN HORMONE AND INSULIN RESISTANCE IN PATIENTS WITH HYPERTHYROIDISM - Bnar S Shexane; Muslih A. Ibrahim (Zanco Journal of Pure and Applied Sciences, 2019)
Carbimazole is one of the common antithyroid drugs for the treatment of hyperthyroidism. It interferes with the synthesis of thyroid hormones and results in the reducing of thyroid hormones level. Apart from determining the effects of carbimazole on serum TSH, T3, T4, insulin, HOMA-IR, HOMA-IS and leptin, the drug effects on corrected QT (QTc) interval duration in hyperthyroidism patients were examined concomitantly Female patients were recruited after obtaining informed consent. Venous blood samples were collected from control healthy subjects and hyperthyroid patients. Treatment with carbimazole results in the improvement of thyroid status and achievement of euthyroidism with a significant decrease in insulin level, and improvement in insulin resistance. The therapy also led to a significant increase in leptin levels. Nonetheless, the non-significant effect on QTc interval duration was observed. In conclusion, this treatment could be beneficial for hyperthyroidism who are at risks of insulin resistance syndrome